HEALING ENVIRONMENTS FOR CHILDREN: AN ENVIRONMENTAL ASSESSMENT OF THE PEDIATRIC WARD AT ALLIED HOSPITAL, FAISALABAD CITY (The Research of Medical Science Review, 2025)
The improved physical environment effects have proven to be positive and healing processes for the wellbeing of patients, visitors and health service providers. The research focused on Pediatric Ward of Allied Hospital Faisalabad as compared to other wards. In-hand study is highly qualitative in the sense, as it focused on peculiar indicators and identified those symbols which influence critical parameters to ascertain physical conducive environment for young children. The rationale for opting environmental assessment of pediatric ward was to furnish a study for improvement in existing facilities relating to environmental degradation taking care of national/international standards. The research identified the impacts of physical resources available to the healing process applied to hospitalized children, including their families as guardians. The preliminary studies were carried out with an interesting argument that was faced and discovered, that how numerous factors currently contribute to the healthcare environment? The primary and secondary data was collected through multiple activities i.e. site visits, interviews, questionnaires, one-to-one meetings, focused group discussions, personal observations, photographs and documentation. The results displayed that over-crowding in ward, excessive patients on single bed, unhygienic conditions, unequal space distribution, thermal discomfort and un-user friendly facilities caused severe ill-effects on children, families and the ward staff. Consequently, efforts were made to establish proper guidelines for spaces layout, general facilities and various environmental variables for the pediatric ward.